IMPLEMENTASI PERIZINAN GALIAN C DI SUNGAI LUK ULO KABUPATEN KEBUMEN - I Kadek Yoga Dana Waskita Putra; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2017)
Illegal mining which often operate in the river sand mining in the Luk Ulo Kebumen often cause a lot of damage to infrastructure at this location. Many roads leading to the mine site into a corrugated perforated and caused frequent traversed by trucks transporting sand from the mine site. The new policy as stipulated in Law No. 23 of 2014 regarding licensing this pleases Excavation C today that the provincial party in all the licensing process and the district are no longer authorized to conduct the regulatory process again because it is already the direct supervisor of the center and very unfortunate again one district only get one supervisor and came from the province so that it can be concluded that the role of the supervisor in his knowledge of the area monitored very minimal and certainly can not be every day watching the mine site. The purpose of this study is to determine how the results of implementation of licensing Excavation C in Kebumen and to know what is the driving factor as well as an obstacle to the passage of the C Excavation licensing policy. The research method in this study is a qualitative research method with data collection technique that is by interview, documentation and observation. While the results of the research were obtained, namely the implementation of the licensing policy of excavation c many walked not in accordance with the Law no.23 of 2014 as well as the increasing number of illegal miners. Such policies should be supervised by the supervisor of the supervisors province has been replaced by the municipal police and with the role of the distribution of the results that have been handed back to the district bestowed on the BAPPENDA the withdrawal of retribution assisted by municipal police in the regulatory process in the field. Recommendations for the community in addressing these issues should people be obedient to the policies that have been prepared for the purpose of the government for the welfare of the community itself. As for the government should make policy decisions should be reviewing the policy in advance in order to minimize the people who will be harmed from the passage of the policy.